Understanding the concept of trust and other factors related to COVID-19 vaccine intentions among Black/African American older adults prior to vaccine development - Orlando O. Harris; Tam E. Perry; Julene K. Johnson; Peter Lichtenberg; Tangy Washington; Bonita Kitt; Michael Shaw; Sahru Keiser; Thi Tran; Leah Vest; Marsha Maloof; Elena Portacolone (Elsevier, 2023)
Background: Black/African Americans are receiving COVID-19 vaccines at much lower rates than whites. However, research is still evolving that explains why these vaccination rates are lower. The aim of this study was to examine the effects of the pandemic among older Black/African Americans, with an emphasis on trust and vaccine intention prior to vaccine development. Methods: Data were collected between July and September 2020 from 8 virtual focus groups in Detroit, MI and San Francisco Bay Area, CA with 33 older African Americans and 11 caregivers of older African Americans with cognitive impairment, supplemented by one virtual meeting with the project's Community Advisory Board. Inductive/deductive content analysis was used to identify themes. Results: Five major themes influenced the intention to be vaccinated: uncertainty, systemic abandonment, decrease in trust, resistance to vaccines, and opportunities for vaccination. The last theme, opportunities for vaccination, emerged as a result of interaction with our CAB while collecting project data after the vaccines were available which provided additional insights about potential opportunities that would promote the uptake of COVID-19 vaccination among older Black/African Americans. The results also include application of the themes to a multi-layer framework for understanding precarity and the development of an Integrated Logic Model for a Public Health Crisis. Conclusions: These findings suggest that trust and culturally relevant information need to be addressed immediately to accelerate vaccine uptake among older Black/African Americans. New initiatives are needed to foster trust and address systemic abandonment from all institutions. In addition, culturally relevant public health campaigns about vaccine uptake are needed. Thus, systemic issues need immediate attention to reduce health disparities associated with COVID-19.